SOCIALLY RESPONSIBLE BUSINESS WITH REFERENCE TO AGRICULTURAL FARMS - Ljiljana Rajnović; Tamara Vujić; Milan Vujić (Ekonomika Poljoprivrede (1979), 2023)
The aim of this paper is to show that business entities that apply ethical principles in their business, gain a good reputation on the market and trust in the quality of their product. Thus, it is known that the business entity is responsible, which enables it to fulfill the basic goal of business, which is to make a profit. The subject of research in this paper is the impact of socially responsible business on the market position of business entities. The authors specifically investigated the application and impact of socially responsible business rules on the position of agricultural farms in the territory of the municipality of Ruma. The instruments used in this research are a survey of farm owners and other stakeholders, an extensive literate review and a method of comparative analysis. The results of the research show that compliance with the rules of business ethics, in the long term, brings more profit to the business entity, so compliance with those standards is becoming more and more universal. That is why agricultural producers follow the rules of socially responsible business. The authors concluded that the social responsibility of business entities is an ethical demand that society places on them, a correlation with two demands that they are already faced with: economic - gaining profit and legal.